Second stage of labor and intraventricular hemorrhage in early preterm infants in the vertex presentation*. (12th April 2013) - Gawade, Prasad L.; Whitcomb, Brian W.; Chasan-Taber, Lisa; Pekow, Penelope S.; Ronnenberg, Alayne G.; Shah, Bhavesh; Plevyak, Michael P.; Markenson, Glenn R.
Abstract: Objective : To investigate the association between exposure to second stage of labor and duration of second stage, and risk of intraventricular hemorrhage (IVH) among infants delivered <30 weeks of gestation. Methods : We conducted a retrospective cohort study among 158 singleton vertex deliveries (97 vaginal and 61 cesarean). Multivariable logistic regression was used to evaluate the risk of IVH related to second stage. Results : Infants exposed to second stage as compared to those not exposed to second stage irrespective of their mode of delivery had increased risk of mild IVH (odds ratio [OR] 2.69; 95% confidence interval [CI] 1.15, 6.29) but not of severe IVH (OR 1.14; 95% CI 0.33, 3.84). No relation with risk of mild (OR 0.98; 95% CI 0.95, 1.01) and severe (OR 1.00; 95% CI 0.95, 1.05) IVH was observed for each 1 min increase in duration of second stage. We also observed no significant association between quartiles of duration of second stage and risk of mild ( p  = 0.20) and severe ( p  = 0.29) IVH. We did not observe any significant interaction by gestational age, chorioamnionitis, birth weight or presenting complaint on admission. Conclusion : The risk of mild IVH was increased in those exposed to a second stage of labor. However, no clear association was observed between duration of second stage and mild or severe IVH.